Demystifying ritual abuse - insights by self-identified victims and health care professionals. Issue 3 (26th May 2020) - Schröder, Johanna; Nick, Susanne; Richter-Appelt, Hertha; Briken, Peer
ABSTRACT: Empirical evidence on organized and ritual child sexual abuse (ORA), that is, organized child sexual abuse with an ideological framework, is rare and definitions of the term "ritual" are often vague or inhomogeneous. The aim of the current study is to analyze contents, purposes and acts of violence in ORA. In a project of the Independent Inquiry into Child Sexual Abuse in Germany, 165 adults who identified themselves as ORA victims as well as 174 health care professionals who supported ORA victims were recruited via various sources and completed anonymous online surveys. Both samples report experiences with ideological frameworks in organized child sexual abuse contexts at the same ratio (88%). Ideologies are mostly perceived as a means to facilitate violent acts (e.g. commercial sexual exploitation). Positive correlations between the manifestation of ideologies and all violent acts suggest that organized and ritual perpetrator groups use the same violent strategies, but ritual or ideological groups, in which perpetrators are more often family members, use them to a greater extent. A modified narrative of "ritual abuse" as a (pseudo-)ideological, domestic and more violent subtype of organized child sexual abuse could enhance the credibility and visibility of ORA in science as well as in society.